2004
DOI: 10.1303/aez.2004.321
|View full text |Cite
|
Sign up to set email alerts
|

Predatory abilities of Amphibolus venator (Klug) (Hemiptera: Reduviidae), a predator of stored-product insect pests

Abstract: The predatory abilities of Amphibolus venator (Klug) on the stored-product insect pest Tribolium confusum Jacquelin du Val were examined. A. venator adults (5-15 days old) were starved for 3 days and then introduced individually into plastic containers containing different prey densities (3, 5, 10, 15 or 20) of last-instar larvae, pupae or adults of T. confusum. The assay was carried out at 25°C and 30°C for 1 day. The number of T. confusum killed by A. venator during 10 days was also investigated a prey densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 11 publications
1
13
0
2
Order By: Relevance
“…Pingale (1954) mentioned that A. venator is an effective agent in the control of C. cautella and A. diaperinus. Nishi et al (2004) in their study report that A. venator hunts larvae, pupae and adults of T. confusum, preferring the first. Predation is more significantly expressed at 30 °C than at 25 °C, because the optimum temperature for breeding and development of A. venator is 30.0-32.5 °C.…”
Section: Insectsmentioning
confidence: 92%
“…Pingale (1954) mentioned that A. venator is an effective agent in the control of C. cautella and A. diaperinus. Nishi et al (2004) in their study report that A. venator hunts larvae, pupae and adults of T. confusum, preferring the first. Predation is more significantly expressed at 30 °C than at 25 °C, because the optimum temperature for breeding and development of A. venator is 30.0-32.5 °C.…”
Section: Insectsmentioning
confidence: 92%
“…Brower et al 9 It has been reported that a X. flavipes adult killed only to 3 late-instar larvae of Tribolium castaneum (Herbst) in 24 h . However, the maximum attack rate in 24 h of a L. campestris adult on the late-instar larvae of T. castaneum was estimated to be 5.0-.7 26 , and that of an A. venator adult on the lateinstar larvae of Tribolium confusum Jacquelin du Val was estimated to be 6.5-4.9 24 . Furthermore, the maximum attack rate of an A. venator adult on T. confusum adults was estimated to be 3.6-27.8, revealing that A. venator is a good predator with regards to T. confusum adults 24 .…”
Section: Predatory Abilities and Suppression Effects 1 Predatory Ranmentioning
confidence: 98%
“…In the present study, we tested the effects of aging on locomotor activity and foraging ability in the assassin bug Amphibolus venator (Klug) [Reduviidae]. A. venator is a carnivorous insect, and they often eat stored-grain insects, including the red flour beetle Tribolium castaneum [16]. We hypothesized that if A. venator also shows decreased locomotor activity with age, then foraging ability could decrease with age as well.…”
Section: Introductionmentioning
confidence: 99%